(3GdJfbjH Ydi eG aj GdebGeGJ ef GdZQjH (B-(3ebGeGJ GdMQjQjs - (3CHi YHO Gddg eMeO Hf YHO Gddg Hf eMeO Hf XaQ GdUbdjs; (3GHf XaQ,J (B565 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf GdYde CQaY fSH hCfaY ecJSH hEf JCKjQ GdYdeGA ai GdCfGe cJCKjQ GdCdHGH ai GdCLSGe deG YGjfhg ef ENdGO GdfahS Edi CMdGe GdOYI hYOe EMSGSgG HBdGe GdVYI cGdPi UfYg s
(3BNQgG (B:s
(3hGSJhba Gddg dCed JhLg EdjfG bhGg hCYhP Hg ef Yed de jeSc Ydi JbhGg agh MSHfG hfYe Gdhcjd GdMeO ddg Ydi CefjI COfGgG aHdZgG hfYeI SfjI SfGgG aShZgG s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs